TBIO-22. A NOVEL PEDIATRIC IDH1 MUTANT GLIOBLASTOMA CELL LINE AND XENOGRAFT MODEL. Issue 2 (22nd June 2018) - Metselaar, Dennis; Meel, Michaël; Waranecki, Piotr; Zwaan, Kenn; Poddighe, Pino; van Vuurden, Dannis; Kaspers, Gertjan; Hulleman, Esther
Abstract: The isocitrate dehydrogenase-1 (IDH1) mutation serves as a hallmark for secondary high-grade gliomas, occurring in over 75% of all secondary glioblastomas (GBM) in adults. IDH1 mutations in pediatric high-grade gliomas are much rarer, and its role is still largely unknown. The lack of biologically representative in vitro and in vivo IDH1 mutant models makes it a difficult to study malignancy. Here we describe the establishment of a pediatric endogenous IDH1 mutant GBM primary cell line (VUMC-HGG-09) derived from an 11 year old female patient. We effectively cultured the VUMC-HGG-09 cells both as neurospheres in a serum-free environment, and as an adherent monolayer in serum enriched medium. VUMC-HGG-09 cells were orthotopically injected into brains of athymic nude mice, which caused successful engraftment and aggressively growing tumors in all the animals. Hematoxylin and vimentin staining showed a diffuse GBM like growth pattern through the whole brain. Furthermore, presence of the human R132H IDH1 mutation was confirmed by immunohistochemistry of the resected mouse brains. Shallow sequencing, whole chromosome painting FISH, and SNP-array were used to map chromosomal aberrations. These data revealed a rarely found chromothripsis like pattern within chromosome 7 and several minor deletions and translocations among other chromosomes. The VUMC-HGG-09 is a unique model that to our knowledge represents the first in vitro and in vivo pediatric IDH1 mutant glioma model. Therefore, VUMC-HGG-09 could serve both as a pediatric GBM cell culture model, as well as a novel in vitro and in vivo model to study the mechanistics of IDH1 mutant tumors.